Risk Factors for Delirium After Spine Surgery in Extremely Elderly Patients Aged 80 Years or Older and Review of the Literature: Japan Association of Spine Surgeons with Ambition Multicenter Study. (September 2017) - Kobayashi, Kazuyoshi; Imagama, Shiro; Ando, Kei; Ishiguro, Naoki; Yamashita, Masaomi; Eguchi, Yawara; Matsumoto, Morio; Ishii, Ken; Hikata, Tomohiro; Seki, Shoji; Terai, Hidetomi; Suzuki, Akinobu; et al.
Study Design: Retrospective database analysis. Objective: Spine surgeries in elderly patients have increased in recent years due to aging of society and recent advances in surgical techniques, and postoperative complications have become more of a concern. Postoperative delirium is a common complication in elderly patients that impairs recovery and increases morbidity and mortality. The objective of the study was to analyze postoperative delirium associated with spine surgery in patients aged 80 years or older with cervical, thoracic, and lumbar lesions. Methods: A retrospective multicenter study was performed in 262 patients 80 years of age or older who underwent spine surgeries at 35 facilities. Postoperative complications, incidence of postoperative delirium, and hazard ratios of patient-specific and surgical risk factors were examined. Results: Postoperative complications occurred in 59 of the 262 spine surgeries (23%). Postoperative delirium was the most frequent complication, occurring in 15 of 262 patients (5.7%), and was significantly associated with hypertension, cerebrovascular disease, cervical lesion surgery, and greater estimated blood loss ( P < .05). In multivariate logistic regression using perioperative factors, cervical lesion surgery (odds ratio = 4.27, P < .05) and estimated blood loss ≥300 mL (odds ratio = 4.52, P < .05) were significantly associated with postoperative delirium. Conclusions: Cervical lesion surgery and greater blood loss were perioperative risk factors for delirium in extremely elderly patients after spine surgery. Hypertension and cerebrovascular disease were significant risk factors for postoperative delirium, and careful management is required for patients with such risk factors.